INTEGRASI NILAI-NILAI ISLAM DI SETIAP MATA PELAJARAN: Pemetaan Model Dan Tantangan Implementasi Kurikulum Merdeka - Muhammad Iqbal Dewantara (BAMALA Institute, 2024)
This study addresses the growing need for integrating Islamic values across subjects within the Merdeka Curriculum, as previous research has predominantly focused on Islamic Religious Education (PAI) alone. The purpose of this research is to map the level of Islamic value integration across various subjects, identify integration models, and explore implementation challenges. This qualitative case study involved 15 teachers from five subjects in three secondary schools, selected through purposive sampling. Data were collected via in-depth interviews, classroom observations, and document analysis, with validity ensured through member checking and reliability tested using intercoder agreement. Data were analyzed thematically using NVivo 12. Results indicate the highest integration levels in PAI (70%) and Social Studies (65%), and the lowest in Mathematics (25%) and Science (28%), with three dominant integration models: thematic, project-based, and local-contextual. These findings extend Content Integration theory by offering a new conceptual model and recommend strengthening cross-subject teacher training for effective value integration.